2002
DOI: 10.1088/0957-4484/14/1/304
|View full text |Cite
|
Sign up to set email alerts
|

Spatial mapping of the electron eigenfunctions in InAs self-assembled quantum dots by magnetotunnelling

Abstract: We use magnetotunnelling spectroscopy as a non-invasive probe to produce two-dimensional spatial images of the probability density of an electron confined in a self-assembled semiconductor quantum dot. The images reveal clearly the elliptical symmetry of the ground state and the characteristic lobes of the higher energy states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…This leads to a spectrum of discrete energy levels, similar to that of atoms. [1][2][3][4][5][6][7] The analogy with atoms is strengthened by the observation of excitonic and electronic states with s-, p-, and d-like character, all of which have been observed in optical 6 and tunneling 8,9 spectroscopy studies. In addition, optical pumping experiments have provided evidence for shell-like filling of the electronic orbitals.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This leads to a spectrum of discrete energy levels, similar to that of atoms. [1][2][3][4][5][6][7] The analogy with atoms is strengthened by the observation of excitonic and electronic states with s-, p-, and d-like character, all of which have been observed in optical 6 and tunneling 8,9 spectroscopy studies. In addition, optical pumping experiments have provided evidence for shell-like filling of the electronic orbitals.…”
mentioning
confidence: 99%
“…8,9,17,18 We attribute this to the fact that the energy levels of the QD ground states lie below the chemical potential in the emitter at all biases so energy-conserving tunneling transitions through the dots are not allowed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The scanning tunneling microscope (STM) is an ideal tool for such characterization as it is capable of atomic-scale spatial resolution [4][5][6]. Spectroscopic studies have been reported recently [7,8]. However, individual 0D eigenstates have not yet been studied by local density of states (LDOS) imaging.…”
mentioning
confidence: 99%
“…We use magneto-tunnelling spectroscopy (MTS) to explore in further detail the nature of the admixed states. The MTS technique has been previously used to study the electronic properties of a number of di erent semiconductor heterostructures [8][9][10] including valence band QWs [8] and quantum dots [10]. Also, this technique allowed us to probe the electronic properties of a GaAs 1−y N y QW layer with y ∼ 2% [11].…”
Section: Resultsmentioning
confidence: 99%